The influence of perceived social risk and buying behaviour on apparel store choice decision among generation Y female students within the Sedibeng district - Maziriri, Eugine Tafadzwa (My University, 2016)
Store choice has become an area of concern for a retailer, with no clear verdict as to what drives customers in the selection of a store. Shopping at the right store with the right social reputation may be essential for many customers. Therefore, the dynamic store choice decision can be conceptualised as a problem of deciding where and when to shop. The primary objective of this study was to determine the influence of perceived social risk and buying behaviour on apparel retail store choice among Generation Y female students within the Sedibeng district. This study focused on perceived social risk, as the literature shows that publically consumed products are the ones with a high level of social risk and the consumer’s need for social acceptance with regards to brand and store choices. This study also looked at the buying behaviour of apparel by Generation Y female students within the Sedibeng district because in today’s increasingly complex retail environment, an understanding of consumers’ buying behaviour and their knowledge of products and services is critical for high quality business decisions. In addition, an understanding of consumers’ buying behaviour will assist retailers to segment their client base and target specific customer groups with strategies designed to meet their retail needs. A quantitative research approach was used for this study and a non-probability convenience sampling procedure was adopted in this study. A structured questionnaire was utilised to survey 400 students from the two universities in the Sedibeng district. The target population for this study was restricted to Generation Y female students within the two universities, namely Vaal University of Technology (VUT) and North West University (NWU). Pre-testing and a pilot study preceded the main survey and reliabilities were measured using the Cronbach alpha coefficients. Out of 400 questionnaires sent to the participants, a total of 370 responses were received and this resulted in a return rate of 92.5 percent for the main study. The statistical analysis of the collected data included descriptive statistical analysis, correlation analysis, exploratory factor analysis, confirmatory factor analysis and structural equation modelling to test the posited hypothesis. The analysis results of the factor analysis showed that based on the Kaiser-Guttman rule, for each of the constructs (perceived social risk, buying behaviour and retail store choice) only two factors that have intrinsic value greater than one were extracted. For the perceived social risk construct, two factors, which were labelled anxiousness and significant others were extracted and for the buying behaviour construct two factors, which were labelled acceptance and reaction were extracted. Lastly, for the retail store choice construct, two factors, which were labelled word of mouth as well as convenience and physical characteristics of the store were extracted through the exploratory factor analysis technique. According to the results of the structural equation modelling analysis, the tested relationships produced satisfactory results consistent with how they were hypothesised. Specifically, it appeared that there is a direct relationship between perceived social risk and buying behaviour. Buying behaviour also has a positive effect on retail store choice and finally, perceived social risk has a good impact, but there is no significant influence on retail store choice as indicated by the findings. Insights gained from this study will assist marketers of apparel products to increase the patronage levels in their stores by expediting the factors identified in this study. Moreover, these findings may enable apparel retail store managers to comprehensively understand how perceived social risk influences a consumer’s retail store choice and to predict as well as develop a current view of the buying behaviour of female Generation Y consumers, thereby facilitating the evelopment and implementation of more effective marketing strategies in their stores. Implications of the findings are discussed and limitations and future research directions are alluded to.
M.. Tech. (Business Administration, Faculty of Management Sciences), Vaal University of Technology
Keywords: Store choice; Retailers; Buying behaviour; Generation Y consumers; Marketing strategy; 338.47687; Stores, Retail.; Clothing and dress -- Purchasing